Comparison of the API Candida System with the AUXACOLOR System for Identification of Common Yeast Pathogens - Campbell, Colin K. (American Society for Microbiology, 1999)
Two commercial systems for the identification of yeasts were evaluated by using 159 clinical isolates that had also been identified by conventional biochemical and morphological methods. The API Candida system correctly identified 146 isolates (91.8%), and the AUXACOLOR system correctly identified 145 isolates (91.2%). However, of the 146 isolates identified by the API Candida system, 23 required supplemental biochemical tests or morphological assessment to obtain the correct identification. The AUXACOLOR system gave no identification in 13 cases (8.2%), while the API Candida system gave an unreadable profile in only one case. Incorrect identifications were more common with the API Candida system (12 isolates; 7.5%) than with the AUXACOLOR system (1 isolate; 0.6%).